LGG-20. Defining subgroups in low grade gliomas by their immune and stromal microenvironment. (3rd June 2022) - Körner, Meik; Spohn, Michael; Schüller, Ulrich; Bockmayr, Michael
Abstract: Immunologic treatment options are still uncommon in low grade gliomas, although such therapies might be beneficial for inoperable and aggressive cases. Knowledge on immune and stromal cells in low grade gliomas, which is a mandatory prerequisite for such approaches, is still scarce. We therefore gathered published gene-expression data from 400 low grade gliomas as well as 302 high grade gliomas in order to quantify 10 microenvironment cell populations. First, we investigated general differences in the microenvironment of low- and high-grade gliomas. Lower-grade and high-grade tumors cluster together, respectively, and show a general similarity within and distinct differences between these groups, the main difference being a higher infiltration of fibroblasts and T-cells in high-grade gliomas. Among the analysed entities, gangliogliomas and pleomorphic xanthoastrocytomas presented the highest overall immune cell infiltration. Further analyses of the low-grade gliomas presented three distinct microenvironmental signatures of immune cell infiltration, which can be divided into T-cell/dendritic/natural killer cell-, neutrophilic/B lineage/natural killer cell-, and monocytic/vascular/stromal-dominated immune clusters. These clusters correlated with tumor location, age, and histological diagnosis, but not with sex or progression-free survival. Our work shows that low- and high-grade gliomas can be characterized and differentiated by their immune cell infiltration. Low grade gliomas cluster into three distinct immunologic tumor microenvironments, which may be of further interest for upcoming immunotherapeutic research.